Autologous peroneus longus tendon graft for superior fulcrum reconstruction: Maintained prospective 1-year outcomes at short-term final follow-up - Kehao Wang; Cheng Peng; Lingchao Kong; Rende Ning; Zheng Zhu; Junke Wang; Guang Chen; Run Fang; Bizhi Tu (PLoS ONE, 2025)
Background Massive irreparable rotator cuff tears (MIRCTs) present challenges in terms of traditional treatments and can result in pain and functional impairment. Due to the limitations of traditional treatments for MIRCTs, alternative options such as superior fulcrum reconstruction (SFR) using the autologous peroneus longus tendon (PLT) have been explored. This study aims to evaluate the clinical and radiographic outcomes of SFR with autologous PLT grafts for the treatment of MIRCTs after a minimum follow-up period of 1 year. Methods This was a prospective cohort study. Thirty-six patients with MIRCTs who underwent arthroscopic SFR with PLT grafts were enrolled and prospectively followed for a minimum of 1 year. Clinical and radiographic evaluations were performed preoperatively and at 3, 6, and 12 months postoperatively. Follow-up evaluations included assessments using the American Shoulder and Elbow Surgeons (ASES) score, Subjective Shoulder Value (SSV), visual analog scale (VAS), Quick-Disabilities of the Arm, Shoulder, and Hand (DASH) score, and measurements of shoulder joint range of motion. Radiography and MRI were used to evaluate the acromiohumeral distance (AHD), Hamada grade, and graft integrity. Repeated measures ANOVA was used to analyze the within-group and between-group differences under different conditions, followed by Bonferroni post-hoc tests to compare outcomes in the postoperative alignment subgroups. Results At the 1-year assessment (n = 36), 34 patients (94.4%) healed well and 2 (5.6%) had MRI-confirmed graft failure. Significant improvements were observed in ASES, QuickDASH, SSV, VAS, forward flexion, external rotation, internal rotation, and AHD scores (all P < 0.05). The use of autologous PLT grafts in SFR resulted in favorable functional outcomes, with a high graft healing rate at the 1-year follow-up. Conclusions Significant improvements were observed in the ASES, QuickDASH, SSV, VAS scores, and shoulder joint range of motion, highlighting the effectiveness of this approach for patients with MIRCTs.